PENYULUHAN TENTANG PENTINGNYA CUCI TANGAN PAKAI SABUN DALAM RANGKA PENINGKATAN PERSONAL HYGIENE PADA ANAK DI TK TURSINA JAYA KELURAHAN SITINJAK - Nurul Hidayah Nasution; Olivia Feby Mon Harahap; Siti Meiranda (Universitas Aufa Royhan Di Kota Padangsidipuan, 2022)
Indonesia is a country that is aggressively improving public health, the government has launched a handwashing with soap (CTPS) program which is useful for improving personal hygiene so that it avoids various diseases. CTPS is far more effective at killing germs, bacteria and viruses than washing your hands with water alone. Hand washing with soap (CTPS) is also known as an effort to prevent disease. This community service aims to increase knowledge and practice of washing hands with soap properly and correctly in kindergarten school children at Tursina Jaya Kindergarten. This community service activity was attended by 30 kindergarten students. This activity was carried out by delivering counseling materials and demonstrations of hand washing with soap. This activity was also interspersed with discussions and questions and answers. The results of this community service activity were received enthusiastically by students. All activity participants stated that this community service was very useful because it could broaden knowledge and the correct practice of washing hands with soap so that it would affect habits in daily life.